Evaluation of antibody response to Goat Pox cell culture vaccine in goats in India (Bangladesh Veterinarian, 2017)
Goat Pox is an important contagious viral disease that causes serious economic loss in small ruminants. The disease causes high morbidity, mortality and trade restriction. Several outbreaks of the disease are reported in Africa and Europe. In India also, the disease has high economic significance. Present study was undertaken to estimate specific antibody response to Live Goat Pox Vaccine in goats. Thirty-five healthy goats were vaccinated with single dose and 10 goats were kept as control. Blood was collected at defined intervals and sera were separated. Virus neutralization test was performed to estimate neutralization index as marker of antibody levels in serum. The study revealed that vaccine could induce immunity against the disease within seven days of vaccination, and reached a peak at 21 days. The titre remained at protective level throughout the oneyear study. Further study can be done to estimate the total duration of immunity through extended study, and the response to challenge with virus.Bangl. vet. 2016. Vol. 33, No. 1, 23-27